Tectonics of Atlantic Canada - Williams, Harold; Dehler, Sonya; Grant, Alan; Oakey, Gordan (Geoscience Canada, 1999)
Summary The tectonic history of Atlantic Canada is summarized according to a model of multiple ocean opening-closing cycles. The modern North Atlantic Ocean is in the opening phase of its cycle. It was preceded by an early Paleozoic lapetus Ocean whose cycle led to formation of the Appalachian Orogen. lapetus was preceded by the Neoproterozoic Uranus Ocean whose cycle led to formation of the Grenville Orogen. The phenomenon of coincident, or almost coincident orogens and modern continental margins that relate to repeated ocean opening-closing cycles is called the Accordion Effect. An understanding of the North Atlantic Ocean and its continental margins provides insights into the nature of lapetus and the evolution of the Appalachian Orogen. Likewise, an understanding of lapetus and the Appalachian Orogen raises questions about Uranus and the development of the Grenville Orogen. Modern tectonic patterns in the North Atlantic may have been determined by events that began before 1000 m.y.